(untitled) (Journal of Parents and Teachers, 2014)
This article talks about Anorexia Nervosa, Bulimia Nervosa and other non-specific eating disorders. It briefly explains what they are and what are the reasons why they appear (criticism, bad experiences, environment, etc.). There is a section dedicated to explaining how to detect if you have an eating disorder (E.D.) according to physique, emotions, and behaviors. Finally, it offers advice for the individual who has an E.D., for the individual’s family, and also offers advice on how to prevent someone from developing an E.D.